Impact of the seismo-volcanic crisis offshore Mayotte on the Dziani Dzaha Lake - Cadeau, Pierre; Jézéquel, Didier; Groleau, Alexis; Di Muro, Andrea; Ader, Magali (Comptes Rendus. Géoscience)
Since May 2018, an unexpected long and intense seismic crisis started offshore Mayotte (Indian Ocean, France). This ongoing seismic sequence is associated with the birth of a newly discovered submarine volcano 50 km east of Petite Terre. Here, we investigate the indirect impact of this crisis on the stability of an atypical ecosystem located in Mayotte, the Dziani Dzaha Lake. This lacustrine system presented physical, chemical and biogeochemical characteristics that were distinct from those classically observed in modern lakes or seawater, e.g. high salinity (up to 70 psu), lack of nitrate, sulfate content below 3 mM, and permanent water column anoxia below ca. 1.5 m depth (2012–2017 period). Based on three surveys conducted in 2020 and 2021, we documented an episode of water column oxygenation, a significant pH decrease and an impressive change in the carbon isotope signatures. These preliminary data suggest that the functioning of biogeochemical cycles in the Dziani Dzaha Lake is impacted by increased CO2 inputs and the changes in the lake mixing dynamics, which is an indirect consequence of the ongoing seismo-volcanic crisis.